Львівський мистець Леонард Марконі - Бірюльов, Ю. (Студії мистецтвознавчі, 2011)
У статті розглянуто творчість скульптора й архітектора Леонарда Марконі (1835–1899) – засновника і одного з чільних представників львівської школи монументально-декоративної скульптури ХІХ ст. This article is devoted to the analysis of the creative work of the sculptor and architect Leonard Marconi (1835–1899). He created a school of monumental decorative sculpture of the XIXth, that is very important for Lviv.